Prevalence of Associated Lesions in Anterior Cruciate Ligament Reconstruction: Correlation With Surgical Timing and With Patient Age, Sex, and Body Mass Index. (December 2015) - Brambilla, Lorenzo; Pulici, Luca; Carimati, Giulia; Quaglia, Alessandro; Prospero, Emanuele; Bait, Corrado; Morenghi, Emanuela; Portinaro, Nicola; Denti, Matteo; Volpi, Piero
Background: Knee instability resulting from anterior cruciate ligament (ACL) rupture is an important risk factor for the onset of meniscal tears and cartilage injuries. A delay of the ligament reconstruction further increases this risk. There is currently no agreement on the right time for surgical ACL reconstruction. Purpose: To verify the correlation of time to ACL reconstruction, patient age, sex, and body mass index (BMI) with the prevalence of meniscal tears and cartilage injuries, as well as to identify the proper surgical timing to decrease the risk of developing associated injuries. Study Design: Cohort study; Level of evidence, 3. Methods: The medical records of 988 patients who underwent primary ACL reconstruction between January 2010 and May 2014 were analyzed to collect data on the prevalence of meniscal tears and cartilage injuries, surgical timing, and patient sex, age, and BMI. Logistic regression was performed to estimate the association between the prevalence of intra-articular lesions and the independent variables of surgical timing, sex, age, and BMI. Results: The risk of developing at least an associated lesion increased by an average of 0.6% for each month of delay of surgical reconstruction. The odds ratio (OR) for developing an intra-articular lesion was 1.989 (95% CI, 1.403-2.820) in those waiting more than 12 months for ACL reconstruction. A 12-month delay for the intervention nearly doubled the risk of developing a medial meniscal tear (OR, 1.806 [95% CI, 1.317-2.475]) but did not modify the risk for the lateral meniscus (OR, 1.183 [95% CI, 0.847-1.653]). Concerning cartilage lesions, the risk after a 12-month delay increased in the medial compartment (femoral condyle: OR, 2.347 [95% CI, 1.499-3.676]; tibial plateau: OR, 5.574 [95% CI, 1.911-16.258]). In the lateral femoral condyle, the risk became significant in patients who underwent surgery more than 60 months after ACL injury as compared with those treated in the first 3 months (OR, 5.949 [95% CI, 1.825-19.385]). Lateral tibial plateau lesions did not seem to increase significantly. Male sex was a risk factor for the onset of lateral meniscal tears (OR, 2.288 [95% CI, 1.596-3.280]) and medial tears (OR, 1.752 [95% CI, 1.280-2.399]). Older age (OR, 1.017 [95% CI, 1.006-1.029]) and increased BMI (OR, 1.120 [95% CI, 1.072-1.169]) were risk factors for the occurrence of at least 1 associated lesion. Conclusion: ACL reconstruction within 12 months of injury can significantly reduce the risk of meniscal tears and chondral lesions. The close association between BMI and prevalence of associated lesions suggests that attention be paid to patients with an elevated BMI when considering the timing of ACL reconstruction surgery.